IDH-mutant gliomas harbor fewer regulatory T cells in humans and mice. (1st January 2020) - Richardson, Leland G.; Nieman, Linda T.; Stemmer-Rachamimov, Anat O.; Zheng, Xijin S.; Stafford, Khalifa; Nagashima, Hiroaki; Miller, Julie J.; Kiyokawa, Juri; Ting, David T.; Wakimoto, Hiroaki; Cahill, Daniel P.; Choi, Bryan D.; et al.
ABSTRACT: The metabolic gene isocitrate dehydrogenase 1 ( IDH1 ) is commonly mutated in lower grade glioma (LGG) and secondary glioblastoma (GBM). Regulatory T cells (Tregs) play a significant role in the suppression of antitumor immunity in human glioma. Given the importance of Tregs in the overall framework of designing immune-based therapies, a better understanding on their association with IDH mutational status remains of critical clinical importance. Using multispectral imaging analysis, we compared the incidence of Tregs in IDH-mutant and IDH wild-type glioma from patient tumor samples of LGG. An orthotopic IDH-mutant murine model was generated to evaluate the role of mutant IDH on Treg infiltration by immunohistochemistry. When compared to IDH wild-type controls, Tregs are disproportionally underrepresented in mutant disease, even when taken as a proportion of all infiltrating T cells. Our findings suggest that therapeutic agents targeting Tregs may be more appropriate in modulating the immune response to wild-type disease.